Generation and load forecasting for optimization of battery energy management in the context of a nanogrid - João Pedro de Bastos Ferreira (2023)
The dissertation proposal has as its primary objective the development of artificial intelligence algorithms that allow the prediction of photovoltaic production and local load in the context of a nano-grid of a residential area (residence, building, or residential neighborhood). The forecast should estimate very short-term (approx. 3 hrs) and day-ahead (24 hrs) scenarios to enable energy storage to perform peak-shaving, load-shifting, and load-leveling operations.